THE CONTRIBUTION OF THE BLIND PEOPLE TO CULTURE DURING THE PERIOD OF INDEPENDENCE - Bozorov , Furqat (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
The article shows how the Uzbekistan Society of the Blind (UzBS ) preserved and gradually developed cultural life in the early years of independence. [1]. After the decline of 1985–1990, a revival began in 1991–1992 at the Tashkent House of Culture (Jamoliddin Karimov, Habibulla Umarov); "Zilola" became a laureate in 1987, "Xalq Dastasi" in 1991, and the works of Vali Gafurov and Qobil Mirzo were published. In 1993–1994, repair and equipment work was carried out, and in 1995–1996, staged competitions were held.